Golden lion : a novel of heroes in a time of war - Smith, Wilbur A.; Kristian, Giles (Smith, Wilbur A. Courtney series., 2015)
"The son of pirate and merchant Sir Frances Courtney, Henry "Hal" Courtney was raised at sea. When war broke out between the English and the Dutch empires, his father, fighting for the English crown, attacked a fleet of Dutch East India Company ships off the coast of Africa. That bravery was met with betrayal, and Sir Francis was executed. His heartbroken son witnessed his death and dedicated his young adulthood to avenging his father's name. Now, twenty years of war have passed. It is 1784, and a truce has been made between the English and the Dutch, ending the long years of battle on the seas. Hal, too has changed. He has become the captain of his own ship, and is soon to become a father himself. Navigating his crew across the waves of danger, Hal sails his ship, the Golden Bough, from the slave markets of Zanzibar to the pirate-riddled waters of the Indian Ocean in search of fortune and treasure. But though the war is over, the final battle has not been won. Soon, Hal will learn that the more a man achieves, the more he has to lose" --